NITROGEN EXPORT FROM FORESTED AND AGRICULTURAL WATERSHEDS OF SOUTHERN CHILE EXPORTACION DE NITROGENO EN CUENCAS BOSCOSAS Y AGRICOLAS EN EL SUR DE CHILE - Carlos E. Oyarzún (Universidad de Concepción, 2003)
Measuring nutrients fluxes in watersheds with different landuse is important for evaluating the effects of conversion of native forests to agricultural land, and for establishing guidelines for land management. Nitrogen (N) concentrations and fluxes were studied over a 12-month period in four watersheds in the Lake Rupanco basin in the Andean Cordillera and four watersheds located in the Lake Huillinco basin in the Coastal Cordillera of southern Chile. Two watersheds in either lake basins were covered mainly by native rainforests, and the other two had mixed landuse (livestock pastures, subsistence agriculture and shrub-pasture mixtures). In the Lake Rupanco area, the annual transport of NO3-N from forested and agricultural watersheds was 4.9 and 11.0 kg ha-1 yr-1, respectively. Inorganic-N (NO3-N + NH4-N) accounted for 53% and 74% of N transport in forested and agricultural watersheds, respectively. In the Lake Huillinco area, the annual transport of NO3-N was 1.4 and 0.8 kg ha-1 yr-1, respectively, with nitrogen organic forms (DON), prevailing and exported mainly from native forests. The impact of the replacement forests by livestock pasture was clearly reflected in the streamwater NO3-N concentrations and fluxes in the watersheds at the Lake Rupanco basin, probably due to fertilization practices Establecer las concentraciones y flujos de nutrientes en cuencas con diferentes uso del suelo nos permite evaluar los efectos del reemplazo de bosques nativos por tierras agrícolas y entregar recomendaciones para un mejor uso de la tierra. En este trabajo se estudiaron las concentraciones y los flujos de nitrógeno (N) durante un período de 12 meses, en cuatro cuencas localizadas dentro del sistema de drenaje del Lago Rupanco en la Cordillera de los Andes y cuatro cuencas localizadas en la cuenca del lago Huillinco en la Cordillera de la Costa, en el sur de Chile. Dos cuencas, en ambas cordilleras, están caracterizadas principalmente por bosques nativos y otras dos cuencas tienen un uso mixto del suelo con praderas ganaderas, agricultura limitada y praderas-matorrales. En el área del Lago Rupanco, el transporte anual de NO3-N en las cuencas forestadas y agrícolas fue de 4,9 y 11,0 kg ha-1 a-1, respectivamente. El transporte de N-inorgánico (NO3-N + NH4-N) representó el 53% y 74%, en las cuencas forestadas y agrícolas. En el área del lago Huillinco, el transporte anual de NO3-N fue de 1,4 y 0,8 kg ha-1 a-1, respectivamente, prevaleciendo el N-orgánico, exportado principalmente desde los bosques nativos. El impacto del reemplazo de los bosques, principalmente por praderas ganaderas, se reflejó claramente en las concentraciones y flujos de NO3-N en las cuencas del area del lago Rupanco, probablemente debido a las prácticas de fertilización